Report on the participation of the Eötvös Loránd University at the Wielbark Archaeological Field School in Malbork-Wielbark, Poland - Hullám, Dénes; Rácz, Zsófia (Dissertationes Archaeologicae, 2013)
PhD, MA and BA students of the Institute of Archaeological Sciences (Eötvös Loránd University) took part in the Erasmus Archaeological Summer Field School in Malbork-Wielbark, Poland (Fig. 1) in 2012 and 2013. The coordinator of the three years planned Erasmus intensive program is Dr. habil. Jörg Kleemann (Humboldt-Universität zu Berlin) with the partnership of the universities of Poland (Uniwersytet Marie Curie-Skłodowskiej Lublin; Uniwersytet Szczeciński), Germany (Ruhr-Universität, Bochum), the Czech Republic (Univerzita Hradec Králové), Spain (Universidad Autónoma de Madrid) and Hungary (Eötvös Loránd University). News and results of the excavation are available at http://ipwafs.hu-berlin.de.